The yeast linear DNA killer plasmids, pGKL1 and pGKL2, possess terminally attached proteins. - Kikuchi, Y (1984)
The terminal structures of linear DNA killer plasmids from yeast, pGKL1 and pGKL2, were analyzed. Results obtained by exonuclease treatments of these plasmids show that both pGKL plasmids have free hydroxyl 3'-ends and blocked 5'-ends. Electrophoretic analysis of the terminal restriction fragments treated with proteases revealed that pGKL1 and pGKL2 have proteins bound at 5'termini and that the terminal protein of pGKL1 is distinct from that of pGKL2. This is the first linear DNA-terminal protein association found in yeast.